Preparation and Characterization of Silver Nanoparticle Cross-linked Polymeric Cages by Freshwater Cyanobacteria and their Bactericidal Evaluation against Multi-Drug Resistant Bacteria - Kuraganti, Gunaswetha; Edla, Sujatha; Viddamuri, Swetha (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Over the past 60 years, numerous modern types of antibiotics have been developed. Antibiotic overuse has been largely responsible for spreading resistant strains that endangering the public's health at an alarming rate. It prompted the pacing advert of new resistance mechanisms and a lessening in the productivity of treating common infectious. Objectives: The present study emphasizes using cyanobacteria silver nanoparticle conjugates (Ag-NPCs) as a drug delivery system to predominantly control Multi-Drug Resistant bacteria. Materials and Methods: The Ag-NPCs were prepared using a sodium alginate calcium chloride cross-linking process. The Ag-NPCs properties have been characterized by UV-vis-Spectroscopy, FTIR (Fourier Transform Infrared Spectroscopy), Transmission Electron Microscopy (TEM), EDAX (Energy Dispersive Analysis X-Ray), and Scanning Electron Microscopic analysis (SEM) analysis. Results: The SEM and TEM analysis showed that Ag-NPCs have been bio-reduced to the size of 20-22nm that are trapped on the surface. FTIR analysis and EDAX analysis are used to confirm the bio-reduction of Ag-NPCs. The antibacterial activity of Ag-NPCs showed prominent results against four MDR bacteria by exhibiting a zone of inhibition with a range of 2-10 mm.
Keywords: Cyanobacteria; Multi-Drug Resistant bacteria; Cyanobacteria Silver nanoparticle conjugates; Drug delivery system; Antibacterial activity